Sleep quality, mood and performance: A study of elite Brazilian volleyball athletes - Andrade, A.; Bevilacqua, G. G.; Coimbra, D. R.; Pereira, F. S.; Brandt, R. (Journal of Sports Science & Medicine, 2016)
This investigation analyzed the relationships between sleep quality, mood, and game results in the elite athletes participating in Brazilian volleyball competitions. Participants (n = 277 elite Brazilian volleyball athletes, 214 (77.3%) men and 63 (22.7%) women) completed the Brunel Mood Scale (BRUMS) and reported their subjective sleep perception. Athletes with poor sleep quality reported higher scores for confusion compared to athletes with good sleep quality (p < 0.01, d = 0.43). In addition, athletes who lost their game at the time of evaluation showed higher tension (p < 0.01, d = 0.49) and confusion (p < 0.01, d = 0.32) levels compared to athletes who won their game. A regression analysis demonstrated that for each point increase in the confusion level, there was a 19.7% reduction in sleep quality. Multivariate analysis of variance indicated that athletes who slept well, and won their games, had lower tension levels. Further, our results indicated that the athletes` mood associated with their success in the competitions. Therefore, in a competition, it is important that the athletes show good sleep quality, and use techniques and strategies to ease their mood variations.